A comparative study on passive films of Fe–11Cr stainless steel and Fe–20Mn–11.5Al–1.4C–5Cr lightweight steel - Heon-Young Ha; Kyeong-Won Kim; Seong-Jun Park; Chang-Hoon Lee; Tae-Ho Lee; Hyun-Uk Hong; Joonoh Moon (Journal of Materials Research and Technology, 2023)
Fe–20Mn–11.5Al–1.4C–5Cr (wt%) lightweight stainless steel (LWSS) was found to have equivalent or better resistance to pitting corrosion than Fe–11Cr (wt%) stainless steel (SS). The desirable resistance to pitting corrosion of the LWSS alloy was attributed to the formation of protective passive film. On LWSS, an (Al,Fe,Cr)-oxide was formed, and on SS, a (Fe,Cr)-oxide was formed. The passive film of LWSS had a higher Cr + Al content than that of SS. In addition, compared to the passive film of SS, the passive film of LWSS was found to be thick and the concentration of point defects was also low.